A risk assessment on the COVID-19 situation in the Philippines: Implications on the ECQ policy - Stella Luz A. Quimbo; CT Latinazo; John Peabody (University of the Philippines, School of Economics (UPSE), 2020)
COVID-19 risk assessment is multi-faceted. The highly infectious nature of the virus in a naïve population, the high case fatality rate and health system over-burdening each need to be considered in developing a strategy to control the spread of the virus and mitigate its health and economic consequences. This note provides a framework for classifying LGUs by degree of risk and identifies policy options for each risk scenario. It urges the Department of Health (DOH) to: (i) re-assess risk levels of local government units (LGUs), (ii) undertake a 100 percent identification of place of residence of all COVID-19 confirmed cases and 100 percent reporting of number of isolation beds and ventilators by all hospitals, and (iii) develop and immediately implement a COVID-specific disease surveillance protocol, including mass testing, contact tracing, and quarantine. Careful and diligent implementation of these protocols will allow a gradual yet cautious and informed re-opening of the economy.
Keywords: 330; COVID-19; Philippines; risk-assessment